Strategi Pembinaan Akhlak pada Taman Pendidikan Al-Qur’an Anwarul Masaliq Keruak - Hadi, Muhammad Irwan (Lembaga Yasin AlSys, 2021)
This study aims to describe the strategy of moral development at the Al-Qur'an Education Park Anwarul Masaliq Keruak. This study is based on the need for the development of Islamic education strategies. The moral development strategy practiced by the ustaz/ustazah aims to foster the morals of the students. The research method used is descriptive with a qualitative approach, with the research subject of three ustadz/ustazah who are active in learning activities of the Qur'an. Data collection techniques through in-depth interviews, observation and documentation. While the data analysis is done by presenting the data in the form of a systematic narrative. The results of the study indicate that the moral development strategy applied in the learning process is integrated in the following ways: 1) habituation of al-karimah morality towards puberty; 2) practice the discipline of worship; 3) train the feeling of fear of Allah in every deed he does.